Effectiveness of Song-Based Audiovisual Media in Developing Arabic Vocabulary Achievement among Third-Grade Students at Nur Al-Mun'im Islamic Elementary School - Helmiatul Hasanah; Isnol Khotimah (Universitas Al-Amien Prenduan, 2026)
The low mastery of Arabic vocabulary (mufradat) among elementary students is largely caused by monotonous and less contextual teaching methods. This study aims to explore the effectiveness of audio-visual media based on songs in improving the vocabulary mastery of third-grade students at MI Nurul Mun’im. This research employed a qualitative approach using Classroom Action Research (CAR), conducted in one cycle consisting of planning, action, observation, and reflection stages. Data were collected through interviews, tests, documentation, and field findings. The results indicate a significant improvement in students’ vocabulary mastery, as shown by the increase in learning completeness from 60% in the pre-test to 70% in the final evaluation. In addition, students demonstrated higher motivation, active participation, and improved ability to understand and retain vocabulary. The implication of this study suggests that audio-visual song-based media creates a more engaging, interactive, and effective learning environment, making it a viable alternative strategy for teaching Arabic at the elementary level Keywords:audio-visual media, singing method, vocabulary mastery, Arabic language, elementary education